PEREMPUAN SENI TRADISI DAN PENGEMBANGAN MODEL INDUSTRI KREATIF BERBASIS SENI PERTUNJUKAN - Anoegrajekti, Novi; Setyawan, Ikwan; Saputra, Heru S.P.; Macaryus, Sudartomo (Institut Agama Islam Negeri Madura, 2015)
The absence of government policy in supporting the creative industry practice is a factor inhibiting the development of performing arts in Banyuwangi. Diverse local performing arts which if managed properly can become a crutch for the emergence of creative economy. This study aims at describing the struggles of women in the tradition arts and in conceptualizingÂ a creative industry model ba-sed on performing arts. The study employed ethnography. The field data were obtained through interviews with the informants. The interpretation of data used a combination of tradition arts, gender, cultural studies, and creative industry perspectives. The results showed that women of tradition arts in general do not rely their livelihoods on art activitiy. They keep trying to develop creative know-ledge embodied in art creation and innovations. Arts institutions have a develop-ment program to maintain quality. The role of the government is manifested in the forms of policies, facilities, activity forums and infrastructural development. The development of Banyuwangi-style performing arts within the framework of the creative industry can support the realization of the creative economy.Copyright (c) 2015 by KARSA. All right reservedDOI:Â 10.19105/karsa.v23i1.610Â